2018
DOI: 10.3389/fpsyt.2018.00194
|View full text |Cite
|
Sign up to set email alerts
|

Trapped in a Daydream: Daily Elevations in Maladaptive Daydreaming Are Associated With Daily Psychopathological Symptoms

Abstract: Background: Maladaptive Daydreaming (MD) characterizes individuals who engage in vivid, fanciful daydreaming for hours on end, neglecting real-life relationships and responsibilities, resulting in clinical distress and functional impairment. Sufferers have embraced the term MD in cyber-communities devoted to this problem because it seemed to uniquely fit their experience and since existing diagnostic labels and their therapies seemed inadequate. However, scientific research in the field has been scarce, relyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
77
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 80 publications
(110 reference statements)
9
77
0
2
Order By: Relevance
“…Some of the most frequent MD comorbid disorders were obsessive-compulsive disorder, attention deficit hyperactivity disorder (ADHD), anxiety disorders, and depressive disorders. A recent MD research paper published in 2018 by Soffer-Dudek et al showed a relationship between MD and obsessive-compulsive symptoms and possible shared mechanisms [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the most frequent MD comorbid disorders were obsessive-compulsive disorder, attention deficit hyperactivity disorder (ADHD), anxiety disorders, and depressive disorders. A recent MD research paper published in 2018 by Soffer-Dudek et al showed a relationship between MD and obsessive-compulsive symptoms and possible shared mechanisms [6].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, although Somer et al developed the MDS to determine if a person is an MDer or not, there are no guidelines recommending the application of this scale. Moreover, because certain MDers reported experiencing other disorders, such as ADHD, depression, schizophrenia, obsessive-compulsive disorder (OCD), and generalized anxiety disorder (GAD), it is reasonable to suspect that these disorders are related to MD but we still do not know how [6].…”
Section: Introductionmentioning
confidence: 99%
“…Childhood traumatic events such as sexual abuse,parent's separation, violence or illness in childhood are responsible in causing social anxiety (Wilson & Barber, 1981;Bandelow et al, 2004;Soffer-Dudek & Somer, 2018). In addition, increased level of stress and cortisol can also cause anxiety especially in adolescents and young adults (Essex et al, 2010;Romeo, 2013;Laurent, Gilliam, Wright & Fisher, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Anothervery interesting variable that has been found to be significantly correlated in most people with social anxiety disorder is maladaptive daydreaming which can be observed in extensive work done by Sommers (2018), on maladaptive daydreaming. In his many researches at multiple accounts he has found a significant correlation between social anxiety disorder and maladaptive daydreaming (Somer, 2000;Somer & Herscu, 2017;Sommer &Soffer-Dudek, 2018;Somer & Soffer-Dudek, 2018).…”
Section: Existence Of Social Anxiety Disorder In Adults Is Investigatedmentioning
confidence: 99%
See 1 more Smart Citation